Determining the Hosting Capacity of Solar Photovoltaic in a Radial Distribution Network Using an Analytical Approach - Dahal, Suraj; Jha, Ajay Kumar; Bhattarai, Nawraj; Panjiyar, Anil Kumar (Journal of Advanced College of Engineering and Management, 2019)
Integrating high photovoltaic (PV) on distribution grid system has a positive impact by significantly reducing the losses and improving the voltage profile at the same time reducing the pollution of the environment However, integrating high proportions of PV in the distribution grid can bring the grid to its operational limits and result in power quality issues. The maximum PV capacity that can be integrated without incurring any grid impacts is referred to as the PV hosting capacity of the grid. This paper intends to evaluate the hosting capacity of solar PV in Dodhara-Chandani (DoC) distribution feeder as one of the feeder of Integrated Nepal Power System (INPS), considering grid parameters and operating condition in Nepal. Three main criteria were investigated for determining the hosting capacity of PV; reverse power flow, maximum voltage deviation of feeder and current carrying limit of conductor. The analysis has been performed by means of static load-flow simulation in Electrical Transient & Analysis Program (ETAP) and coding in MATLAB R2017a. The study shows that PV of rated capacity 687kWp can be installed at a point of interconnection (POI) whereas an optimal placement of solar PV is found to be at 18th node (in between starting and end of the feeder) considering minimum system losses. The minimum voltage profile at end of the feeder has improved by 8 % while the active power loss reduction of network has reduced by 83.6 % after the integration of solar PV. The results indicate voltage at different buses and the ampacity of most of the conductors have been improved after the integration of PV system into DoC feeder.